Hypertension Treatment in US Long‐Term Nursing Home Residents With and Without Dementia. Issue 10 (22nd July 2019) - Boockvar, Kenneth S.; Song, Wei; Lee, Sei; Intrator, Orna
Abstract : OBJECTIVES: To describe patterns of antihypertensive medication treatment in hypertensive nursing home (NH) residents with and without dementia and determine the association between antihypertensive treatment and outcomes important to individuals with dementia. DESIGN: Observational cohort study. SETTING: All US NHs. PARTICIPANTS: Long‐term NH residents treated for hypertension in the second quarter of 2013, with and without moderate or severe cognitive impairment, as defined by the NH Minimum Data Set (MDS) Cognitive Function Scale. MEASUREMENTS: The primary exposure was intensity of antihypertensive treatment, as defined as number of first‐line antihypertensive medications in Medicare Part D dispensing data. The outcome measures were hospitalization, hospitalization for cardiovascular diseases using Medicare Hierarchical Condition Categories, decline in physical function using the MDS Activities of Daily Living (ADLs) scale, and death during a 180‐day follow‐up period. RESULTS: Of 255 670 NH residents treated for hypertension, 117 732 (46.0%) had moderate or severe cognitive impairment. At baseline, 54.4%, 34.3%, and 11.4% received one, two, and three or more antihypertensive medications, respectively. Moderate or severe cognitive impairment (odds ratio [OR] = 0.80 vs no or mild impairment; P  < .0001), worse physical function (OR = 0.64 worst vs best tertile; P  < .0001), and hospice or less than a 6‐month life expectancy (OR = 0.80; P  < .0001) were associated with receipt of fewer antihypertensive medications. Increased intensity of antihypertensive treatment was associated with small increases in hospitalization (difference per additional medication = 0.24%; 95% confidence interval = 0.03%‐0.45%) and cardiovascular hospitalization (difference per additional medication = 0.30%; 95% confidence interval = 0.21%‐0.39%) and a small decrease in ADL decline (difference per additional medication = −0.46%; 95% confidence interval = −0.67% to −0.25%). There was no significant difference in mortality (difference per additional medication = −0.05%; 95% confidence interval = −0.23% to 0.13%). CONCLUSION: Long‐term NH residents with hypertension do not experience significant benefits from more intensive antihypertensive treatment. Antihypertensive medications are reasonable targets for deintensification in residents in whom this is consistent with goals of care. J Am Geriatr Soc 67:2058–2064, 2019